التطور الفني للزخارف المعمارية في واجهات المباني الإسلامية بليبيا من العهد العثماني حتى بدايات القرن العشرين (Comprehensive Journal of Science, 2025)
This study examines the artistic development of architectural decorations on the façades of Islamic buildings in Libya from the Ottoman conquest in 1551 to the early twentieth century. A comparative analytical approach was applied to investigate decorative characteristics in Tripoli and Ghadames, representing two distinct models: Ottoman-influenced coastal architecture and locally rooted desert architecture. The findings reveal that Libyan architectural decoration is distinguished by a synthesis of Ottoman stylistic elements in Tripoli and simplified geometric and gypsum-based motifs in Ghadames. The study also demonstrates that political, social, and religious transformations—particularly during the Karamanli period—played a significant role in shaping decorative techniques and stylistic preferences. The research concludes with recommendations emphasizing the necessity of digitally documenting historic façades, establishing a national database for Libyan architectural ornamentation, and supporting specialized restoration programs aimed at preserving this unique cultural and architectural heritage.
Keywords: Architectural Ornamentation؛Islamic Architecture؛Ottoman Period؛Tripoli ؛Ghadames